Intraspecific interactions at high predator densities affect the predation efficiency of Neoseiulus californicus (Acari: Phytoseiidae) when prey density is low. (17th May 2022) - Papanikolaou, Nikos E.; Broufas, George D.; Kypraios, Theodore; Liaka, Triantafyllia; Pappas, Maria L.
Abstract: Quantifying functional responses is a cornerstone in evaluating the predation efficiency of biological control agents such as predatory insects and mites. In this study, we investigate whether the efficiency of Neoseiulus californicus (Acari: Phytoseiidae) in consuming prey is driven by intraspecific interactions. For this purpose, laboratory functional response experiments were conducted using one, two, three or four predators at several initial egg densities of the two‐spotted spider mite, Tetranychus urticae (Acari: Tetranychidae). The data fitted to the predator‐dependent Crowley–Martin model which accounts for intraspecific interactions. The results suggest that at high prey densities, i.e. the densities at which the predator is satiated, intraspecific interactions did not affect the predation potential of N . californicus, as the maximum number of T. urticae eggs that can be attacked by predator individuals did not differ between treatments (i.e., predator densities). However, at low prey densities and the highest predator density (i.e., four individuals), intraspecific interactions were detected, as revealed by the estimated attack rates, i.e. the per capita prey consumption at low prey densities. While mean attack rates did not differ significantly when one, two and three predators were exposed to prey, when predator density increased to four individuals, attack rate was considerable lower compared to the other predator densities. These results indicate that intraspecific interactions are more intense at low prey densities, where the predator is not satiated and therefore digestion breaks do not exist. In contrast, at high prey densities digestion breaks exist, so that may fully accommodate the cost of intraspecific interactions. These results also suggest that predator density should be considered when functional responses are measured. Abstract : Fitting of the Crowley–Martin model to Neoseiulus californicus functional response data on Tetranychus urticae eggs. P denotes the predator density.